Protective effect of epigallocatechin gallate on inflammatory bowel disease induced by dextran sulfate sodium in mice - ZHAO Yueling; DING Jian; HE Jia; KONG Dedong; XU Ping; WANG Yuefei (浙江大学学报. 农业与生命科学版)
We established three groups, blank, control and epigallocatechin gallate (EGCG) treatment groups, to explore the effect of EGCG on inflammatory bowel disease (IBD) induced by dextran sulfate sodium (DSS) in mice. The result showed that the spleen size of EGCG treatment group was significantly smaller than that of the control group. The detection of inflammatory factors in intestinal lamina propria cells and colon tissue supernatant in mice showed that EGCG could reduce the expression and secretion of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) (P<0.01), and had no significant effect on interleukin-10 (IL-10) (P>0.05). In addition, EGCG had no obvious effect on the expression of tight junction protein claudin-1 and occludin in intestinal epithelial cells. The hematoxylin-eosin (HE) staining results also showed that there was no significant alteration to the intestinal mucosa and epithelial barrier damage with EGCG. To sum up, EGCG could inhibit inflammatory factor secretion, reduce systemic inflammatory response in mice caused by colon inflammation, and play a protective role in DSS-induced inflammatory bowel disease in mice.